Debating desalination: Stakeholder participation and decision-making in southern California - Ekta J. Patel (Water Alternatives, 2023)
As desalination gains rapid traction worldwide, it is instructive to investigate how various stakeholders debate this water supply infrastructure and how decision-making processes incorporate stakeholder input. This paper conducts a discourse analysis of public comments and official deliberations tied to the permitting of Poseidon Water’s proposed $1.4 billion seawater desalination facility in Huntington Beach, California, which state regulators ultimately denied in May 2022. The facility was the first and largest desalination project to undergo permitting since the state passed desalination-specific legislation in 2015. This paper analyses public hearings between 2020 and 2022 at two key permitting agencies to detail the main storylines that proponents and opponents of this desalination facility used to justify their positions for, or against, the facility. Seven key themes are identified within the storylines. The paper shows that discursive tactics can create temporary openings for desalination debates to be depoliticised or (re)politicised in ways that influence permitting decisions on the margins, but that the decisionmaking process remains largely rigid to stakeholder participation. The results have implications for understanding desalination-specific issue areas for stakeholders and motivating decision-making processes to be more collaborative and engaging with stakeholders on newer water policy issues.